Primary School Teacher’s Understanding and Selfefficacy Towards Implementation of Inquiry-based Instruction in Primary Science Curriculum: Case of Kigali City Rwanda - Niyitegeka, Drocelle (Unnes Science Education Journal, 2020)
This study explored public primary school teachers’ understanding of inquiry based instruction, teachers’ self-efficacy for inquiry based instruction and its actual implementation in upper primary science classroom. Data included servey instrument using everyday teaching sennarios to measure teachers’understanding, self-report servey instrument to measure teachers’ self-efficacy for inquiry based instruction, individuals’ interviews and classroom observation through Electronic Quality of Inquiry Protocol(EQUIP) designed to measure the quality and quantity of inquiry being implemented in science classroom. The results of this study revealed that teachers’ undesrtanding has limited description of the components of inquiry based instruction to only posing and answering the questions in science classroom. They failed to decribe all components of inquiry based instruction as listed in competence based curriculum as the vehicle of the entire learning and teaching process which lead to insufficient understanding of inquiry based instruction. Their self-efficacy for inquiry based instruction is high and their actual implementation is at lowest level, none of the components of inquiry science classroom has implemented by participating teachers. No factors predicting implementation found among teachers ‘understanding of IBI, teachers’ self-efficacy for IBI and their demographic information. Implications for teacher-education and research about self-efficacy and teachers’ understanding are discussed.